Efficacy and prognosis biomarker of locally advanced ESCC patients treated with neoadjuvant chemotherapy and anti-PD-1 immunotherapy - Li, Shuman; Zhou, Jie; Wang, Qianli; Chen, Jiewei; Qi, Yapeng (Frontiers in Oncology, 2025)
IntroductionImmunotherapy has rapidly advanced in tumor treatment. In esophageal squamous cell carcinoma (ESCC), its use in neoadjuvant therapy has shown promising results. Several phase III clinical trials have confirmed that immunodetection site inhibitors in neoadjuvant therapy can enhance the pathologically complete response (pCR) rate.MethodsWe retrospectively analyzed 128 ESCC patients treated with neoadjuvant chemotherapy plus anti-PD-1 immunotherapy at the Affiliated Cancer Hospital of Zhengzhou University and Henan Cancer Hospital from July 2019 to November 2023.ResultsOf the 128 patients, 31 (24.1%) achieved pCR, and 46 (35.9%) achieved a major pathological response (MPR). Female patients, low-level tumor abnormal protein (TAP), and moderate differentiation were significantly associated with a higher pCR rate and MPR rate. Besides pCR rate and MPR rate, low-level TAP and moderate differentiation had significantly longer PFS and OS. The mean PFS in the low-level TAP group was 42.4 months, significantly longer than the 28.5 months in the high-level TAP group (p = 0.019). The mean OS in the low-level TAP group was 43.7 months, compared to 30.5 months in the high-level TAP group (p = 0.027). The multivariate analysis showed that TAP and differentiation were independent prognostic factors for PFS, and the pCR rate was an independent prognostic factor for OS in ESCC patients treated with anti-PD-1. Thus, lower TAP levels predict a better response to neoadjuvant chemotherapy plus anti-PD-1 immunotherapy in advanced ESCC patients. In clinical practice, serum TAP levels before neoadjuvant therapy can serve as a useful tool to predict the efficacy of this combined treatment.